Policy autonomy, coordination or harmonization in the persistently heterogeneous European Union? - Luděk Kouba; Michal Mádr; Danuše Nerudová; Petr Rozmahel (DANUBE: Law, Economics and Social Issues Review, 2016)
Within the context of the continuing integration process in Europe, this paper addresses the question of whether policies in the EU should head towards autonomy, coordination or harmonization. Taking the path dependence effect into account, it is the authors' opinion that Europe has gone too far in its integration process to be able to continue with policies being fully under the competences of individual member countries. However, the habitual question still arises: does fiscal policy need to be harmonized to a level comparable to monetary policy as these two policies, necessarily, complement each other? This paper argues that it does not. There are three main arguments discussed. Firstly, the authors build on the theory of fiscal federalism. Secondly, there are significantly different regimes of welfare states and extents of social policies among European countries, which strongly determine the character of public finance. And thirdly, the tax systems across Europe are also highly divergent, with many features of continuing tax competition.
Keywords: 330; European Union; Fiscal Policy; Heterogeneity; Policy Coordination; Policy Harmonization